PENDEKATAN SAINTIFIK TERHADAP KEMAMPUAN MENULIS NARASI ANAK TUNARUNGU KELAS IV SDLB - ERY MELIANA, DIYAH (Jurnal Pendidikan Khusus, 2016)
ABTRACT This research had purpose to know the influence of scientific approach toward writing narrative ability to the fourth class of hearing impairment students in SDLB PGRI Kawedanan Magetan. The instrument used to obtain the data of writing narrative ability was technique test while for data analysis used Wilcoxon Match Pairs test. The research result indicated that the average value result of pre test was 50,83 and the post test was 76,6. The result of data analysis indicated that Zh value was 2,20 and Z table was 5%, 1,96 so the interpretation was Zh > Zt. It could be concluded that Ha was accepted it meant there was influence of scientific approach application toward writing ability of the fourth class hearing impairment students in SDLB PGRI Kawedanan Magetan. Keywords: Scientific learning approach, writing narrative